Jane Austen among Women - Kaplan, Deborah (Johns Hopkins University Press, 2019)
Originally published in 1992. In an age when genteel women wrote little more than personal letters, how did Jane Austen manage to become a novelist? Was she an isolated genius who rose to fame through sheer talent? Did she draw strength from the support of her family or from women writers who went before her? In Jane Austen among Women, Deborah Kaplan argues that these explanations are either misleading or insufficient. Austen, Kaplan contends, participated actively in a women's culture that promoted female authority and achievement-a culture that not only helped her become a novelist but also influenced her fiction.